STRENGTHENING STUDENT CITIZENSHIP CHARACTER USING PROBLEM-BASED LEARNING MODELS IN THE COVID-19 ERA - Muhammad Akbar Hajuan; Yunita Dwi Pristiani; Agus Widodo; Wikan Sasmita (Sosiohumaniora, 2023)
ABSTRACTEducation is one of the sectors that has felt the most impact from the Covid 19 pandemic. The policy of prohibiting face-to-face learning is a challenge in the education system in Indonesia. Learning which includes cognitive, affective, and psychomotor aspects is not yet optimal and efficient if distance learning is implemented. This is certainly a challenge in itself to be able to pass and carry out various aspects of online learning optimally. One of the successes in the learning process lies in the use of strategies, methods, and learning models. Problem-based learning is a learning model that is proven to be able to improve students' critical thinking skills in solving a problem as strengthening the character of citizenship. This study used the Classroom Action Research method (classroom action research) which involved 36 students of Electronics Engineering, Yogyakarta State University. Data collection was carried out by observation and interview techniques. Data analysis used the Miles & Huberman analysis technique which included data reduction, descriptive presentation, and conclusion. The results of this study indicate that students still have good socio-cultural values, such as mutual respect and respect and have a high awareness of mutual cooperation so that they can recognize new learning phenomena. Have the ability to recognize the values of civic education and online learning culture. Learning Citizenship Education through the Problem-Based Learning Model in Strengthening Citizenship character can strengthen the insights of students who have good character, from the data obtained in the field during the learning process which is categorized as quite good even though it does not always run smoothly in every meeting. This is because problem-based learning is a learning model that moves students' critical thinking characters vary greatly in the implementation of online learning.Keywords: problem-based learning models; citizenship character; COVID-19